Pengaruh Tenaga Kerja, Adopsi Teknologi dan Modal Usaha Terhadap Tingkat Pendapatan Melalui Peningkatan Kapasitas Produksi Pada Usaha Gula Aren di Desa Pakisan Kecamatan Kubutambahan - Dewi, Kadek Indah Surya; Dharmayasa, I Putu Arya (Universitas Pendidikan Ganesha, 2024)
This research aims to analyze the influence of labor, technology adoption, and business capital on income levels through the increase of production capacity as an intervening (mediating) variable in Palm Sugar Enterprises in Pakisan Village, Kubutambahan District. This study uses descriptive analysis and path analysis with a sample of 56 Palm Sugar Entrepreneurs in Pakisan Village, Kubutambahan District. The results of this study reveal that (1) there is an influence of labor on the production capacity of the Palm Sugar Business in Pakisan Village, Kubuaddan District, with tcount 4.341 > tcount 2.010 and sig 0.000 < 0.05; therefore, H0 is rejected, and H1 is accepted, which means that the workforce has a positive effect on the production capacity of the Palm Sugar Business in Pakisan Village, Kubuaddan District. (2) There is an influence of technology adoption on the production capacity of the Palm Sugar Business in Pakisan Village, Kubuaddan District, with tcount 3.173 > ttable 2.010 and sig 0.003 < 0.05; therefore, H0 is rejected, and H2 is accepted, which means that technology adoption has a positive effect on the production capacity of the Sugar Business Sugar palm in Pakisan Village, Kubucepatan District. (3) There is an influence of business capital on the production capacity of the Palm Sugar Business in Pakisan Village, Kubucepatn District, with tcount 3.299 > ttable 2.010 and sig 0.002 < 0.05; therefore, H0 is rejected, and H3 is accepted, which means that business capital has a positive effect on the production capacity of the Sugar Business Sugar palm in Pakisan Village, Kubucepatan District. (4) There is an influence of labor, technology adoption, business capital, and production capacity on the income level of the Palm Sugar Business in Pakisan Village, Kubuaddan District, with Fcount 24.016 > Ftable 2.78 and sig 0.000 < 0.05; therefore, H0 is rejected, and H4 is accepted, which means that labor, technology adoption, business capital, and production capacity have a positive effect on the income level of the Palm Sugar Business in Pakisan Village, Kubuaddan District.